SEDIMENT CHARACTERISTIC AND DISTRIBUTION PATTERN OF WESTERN COAST OF RUPAT STRAIT - Afrizam '; Rifardi '; Irvina Nurrachmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Abstract This research was conducted in May 2014 in the western part of the Rupat strait. The aim of study was to describe the condition of depositional environments in the western part of the Rupat strait. Determination of sampling points done by using purposive sampling method, taking into account the tidal patterns and source of sedimentary material that goes into the waters. The western part of Strait Rupat divided into 12 sampling points. Surface sediments was taken using a grab sampler at all sampling points. Sediment samples were analyzed by using the method of mechanical analysis and the data obtained were processed with analisis. Cluster analysis showed that the study area was divided into three groups (clusters), namely Group I is at the southern and northern of the study area, this area is characterized the strength of the flow of sediment transport the strongest and most stable compared with other groups. Group II was on the edge of the island of Sumatra and Rupat the middle toward the North, this is a transition region between groups I and II were characterized by flow force weaker and more fragile than the first group, but stronger and more stable than group III. Group III were at the edge of the Strait Rupat and Rupat, this area is characterized by the flow of sediment transport the weakest and most unstable compared to other groups.Keyword : Sediment, Characteristics, Distribution Pattern, Rupat Strait